PENDEKATAN GURU SEJARAH DALAM IMPLEMENTASI PENDIDIKAN KARAKTER: STUDI DESKRIPTIF DI SMA NEGERI 4 BENGKULU SELATAN - Een Syaputra; Ririn Selvianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
This study aims to describe and analyze the approach of history teachers in the implementation of character education at SMA Negeri 4 Bengkulu Selatan. This study used a qualitative research design with a descriptive tife. This research was conducted at SMA negeri 4 Bengkulu Selatan. Dara were collected by in-depth inteviews, document analysis and observation. The data analysis was carried out using Milleas & Huberman’s Interactive Model, which consists of three stages: data reduction, data presentation, and conclution. Based on the research that has been done, the following results were fount: 1) the implementation od character education in history learning at SMA Negeri 4 Bengkulu Selatan was carried out using two main approach, namely the integrated learning approach and habituating approach; 2) an integrated approach to learning is carried out with four main strategies, namely value analysis, value clarification, storytelling method and cooperative learning model; 3) the habituating approach is carried out with three main strategies, namely praying before and after stuying, time discipline, and shaking hand.